IMPLEMENTATION OF COMPENSATION FOR LOSS OF OFFICIAL VEHICLES IN ROKAN HILIR DISTRICT - syahri, alfi; ardiansah, ardiansah; Kadaryanto, Bagio (EKSEKUSI, 2024)
Article 7 of Government Regulation Number 38 of 2016 concerning Procedures for Compensation Claims for State/Regional Losses Against Non-Treasurer Civil Servants or Other Officials, states that: "Based on the verification results report as intended in Article 5 paragraph (3), the State/Regional Loss Settlement Official must resolve State/Regional Losses by carrying out Compensation Claims." However, in the Rokan Hilir Regency government environment, the implementation is not yet underway because the demand for regional compensation for 4 non-Treasurer Civil Servants who lost two-wheeled official vehicles has not been implemented. The aim of this research is to analyze the implementation of compensation for loss of official vehicles in Rokan Hilir Regency, to analyze the obstacles and efforts. This type of research is sociological/empirical legal research. The results of the research show that the implementation of compensation for loss of official vehicles in Rokan Hilir Regency based on Government Regulation Number 38 of 2016 concerning Procedures for Claiming State/Regional Compensation Against Non-Treasurer Civil Servants or Other Officials has not been implemented in accordance with applicable legal provisions. This was proven by 4 non-treasurer civil servants who lost their two-wheeled official vehicles, causing regional financial losses, but their demands for regional compensation for losses have not yet been implemented.Keywords: Official Vehicles, Losses, Claims